Temporal attention is not affected by working memory load. (September 2020) - Zanto, Theodore P.; Liu, Helen; Pan, Peter; Gazzaley, Adam
Abstract: Temporal attention refers to the ability to orient attention in time, which serves to enhance performance such as target detection and discrimination and is a fundamental component of cognitive function. Although some research indicates that temporal attention ability is affected by working memory updating, it is unclear whether temporal attention is also affected by the availability of working memory stores. To address this, participants were presented a dual-task paradigm requiring zero, three, or six digits to be held in working memory while engaged in a temporally cued visual discrimination task. Results show that working memory load did not differentially affect the ability to benefit from predictive temporal cues during the visual discrimination task. This indicates that temporal attention is not affected by available working memory stores. Interestingly, posterior beta band (12–30 Hz) activity was differentially modulated by temporal attention and working memory load, such that it decreased prior to expected targets and increased with load. Analysis across participants indicated that those individuals who exhibited greater temporal attention-based modulation of beta activity (i.e., predictive < neutrally cued) displayed improved discrimination performance, but also yielded lowered working memory accuracy. Thus, the ability to benefit from temporal attention processes while multitasking comes at the cost of lowered secondary task performance. Together, these results indicate that available working memory stores do not affect temporal attention ability. Rather, limitations in divided attention ability result in a performance cost that prioritizes one task over another, which may be indexed by beta band activity.